The Influence of CYP3A4 Genetic Polymorphism and Proton Pump Inhibitors on Osimertinib Metabolism - Gao, Nanyong; Zhang, Xiaodan; Hu, Xiaoqin; Kong, Qihui; Cai, Jianping; Hu, Guoxin; Qian, Jianchang (Frontiers in Pharmacology, 2022)
The aim of this study was to (i) investigate the effects of 27 CYP3A4 variants on the metabolism of osimertinib and to (ii) study the interactions between osimertinib and others as well as the underlying mechanism. A recombinant human CYP3A4 enzymatic incubation system was developed and employed to determine the kinetic profile of CYP3A4 variants. Ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) was applied to detect the concentration of the main metabolite, AZ5104. The results demonstrated that the relative clearance rates of CYP3A4.19, 10, 18, 5, 16, 14, 11, 2, 13, 12, 7, 8, and 17 in catalyzing osimertinib were significantly reduced to a minimum of 25.68% compared to CYP3A4.1, while those of CYP3A4.29, 32, 33, 28, 15, 34, and 3 were obviously enhanced, ranging from 114.14% to 284.52%. The activities of the remaining variants were almost equal to that of CYP3A4.1. In addition, 114 drugs were screened to determine the potential interaction with osimertinib based on RLM reaction system. Sixteen of them inhibited the production of AZ5104 to 20% or less, especially proton pump inhibitors, among which the IC50 of rabeprazole was 6.49 ± 1.17 μM in RLM and 20.39 ± 2.32 μM in HLM, with both following competitive and non-competitive mixed mechanism. In an in vivo study, SD rats were randomly divided into groups, with six animals per group, receiving osimertinib with or without rabeprazole, omeprazole, and lansoprazole. We found that the AUC (0-t), AUC (0-∞), and Cmax of osimertinib decreased significantly after co-administration with rabeprazole orally, but they increased remarkably when administered through intraperitoneal injection. Taken together, our data demonstrate that the genetic polymorphism and proton pump inhibitors remarkably influence the disposition of osimertinib, thereby providing basic data for precise application of osimertinib.